Thermal behaviour of poly(methyl methacrylate)/fullerene composite films. (3rd August 2018) - Alekseeva, Olga V.; Noskov, Andrew V.; Guseynov, Sabir S.
ABSTRACT: Poly(methyl methacrylate) films and poly(methyl methacrylate)/fullerene composite films were fabricated by casting from toluene solutions. The mass fraction of fullerene (C60 ) was varied from 0.05–3 wt. %. The effect of the fullerene (C60 ) content on the thermal degradation parameters of the composite films was evaluated by thermogravimetric (TG) analysis. It was found that the incorporation of C60 improved the thermal stability of the polymers. The films eventually decomposed in three stages. Incorporation of fullerene caused a change in the distribution of mass loss over the stages of degradation in comparison with the pristine polymer. Using differential scanning calorimetry (DSC), the phase transitions from the glassy state to the elastic one was studied for the examined polymeric materials. New data relating to the effect of C60 on the glass transition temperature of composites with low weight fractions of filler were obtained. Specifically, for films containing up to 0.1 wt. % of C60, a single glass transition temperature was found, whereas for composites with a higher concentration of filler, two glass transition temperatures were recorded.